Deployment Of High Speed Broadband (HSBB) Initiative In Malaysia : A Case Study On Telekom Malaysia Berhad - Zulkifli, Hafizulrahman (2009)
The purpose of this paper is to explain what HSBB is all about and study how TM carries out the deployment of this massive project. The paper also discusses the project benefits and challenges, and how TM manages HSBB technologies, systems, strategies and policies in order to successfully deploy the project off the ground.